The Estimation of Reservoir Brine Properties During Crude Oil Production Using a Simple Predictive Tool - Bahadori, Alireza; Al-Haddabi, M.; Vuthaluru, Hari (Taylor & Francis Group, 2013)
Most oil wells eventually produce some quantity of reservoir brine (formation water) over their lifetime. Increased water production is usually indicated by a significant increase in the water to oil ratio (WOR) of the well. As the WOR of well increases, it causes costly added water handling, it reduces efficiency of the depletion mechanism, the afflicted well may be abandoned early, there can be loss of the total field overall recovery, and because reservoir brine (formation water) is corrosive its disposal becomes expensive. In this work, a simple Arrhenius type function is presented for estimation of reservoir brine (formation water) properties for temperatures above 30°C and salt contents between 5% and 25% by mass. An Arrhenius type function has been selected because it is easier than existing approaches, less complicated with fewer computations, and suitable for engineers. These expressions can then be incorporated into further calculations that require predictions of reservoir brine (formation water) properties as functions of temperature and salt content. Estimations are found to be in excellent agreement with the reliable data in the literature with average absolute deviation being around 0.09–2.6%. The tool developed in this study can be useful for the petroleum engineers to have a quick check on the reservoir brine properties at various conditions without opting for any experimental measurements. In particular, chemical and petroleum engineers would find the proposed approach to be user-friendly with transparent calculations involving no complex expressions.